2015
DOI: 10.1002/tea.21258
|View full text |Cite
|
Sign up to set email alerts
|

Long-term conceptual retrieval by college biology majors following model-based instruction

Abstract: One of the goals of college-level introductory biology is to establish a foundation of knowledge and skills that can be built upon throughout a biology curriculum. In a reformed introductory biology course, we used iterative model construction as a pedagogical tool to promote students' understanding about conceptual connections, particularly those linking genetic variation to organismal fitness. In interviews conducted 2.5 years later, we examined students' retrieval of conceptual connections emphasized during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 68 publications
0
21
0
Order By: Relevance
“…Fifth, related to this, it is important to note that our “knowledge” measure was one representing content knowledge and immediate recall of that knowledge following the program. Researchers have identified the need to better promote long‐term science knowledge (Dauer & Long, ; Shemwell, Avargil, & Capps, ) and so future research would do well to collect knowledge data some months following a target education program. Sixth, given the program was multifaceted, with different stations and different resources and prompts at each station, it would be useful to know if one station or one form of resource yielded relatively greater impact on outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, related to this, it is important to note that our “knowledge” measure was one representing content knowledge and immediate recall of that knowledge following the program. Researchers have identified the need to better promote long‐term science knowledge (Dauer & Long, ; Shemwell, Avargil, & Capps, ) and so future research would do well to collect knowledge data some months following a target education program. Sixth, given the program was multifaceted, with different stations and different resources and prompts at each station, it would be useful to know if one station or one form of resource yielded relatively greater impact on outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…To improve ST teaching and learning, we suggest educators view ST on a continuum of development rather than as a binary of correct/incorrect or present/absent at one point in time. Recent research suggests that ST is constructed over time as new information is obtained and new connections across information are made [14]. Therefore, to understand the development of ST, we should measure it repeatedly, over time within a classroom or within a curriculum and adapt instruction to specific challenges that student's face as they represent their understandings of a system.…”
Section: Systems Thinking On a Continuummentioning
confidence: 99%
“…In a larger study, Dauer et al described changes in student-constructed "gene-to-evolution" cognitive maps and explanations over a semester of an introductory biology course [28], and Dauer and Long characterized changes in student thinking and explanation quality 2.5 years after the introductory biology course [14]. In the longitudinal study, the authors identified distinct groups of learners by combining analysis of the cognitive maps with other formal written and verbal assessments to characterize changes in student thinking over time.…”
Section: Assessing Systems Thinking By Evaluating Cognitive Mapsmentioning
confidence: 99%
“…Concept mapping and other visual representations illustrate both students’ deep content understandings and their misconceptions (Mintzes et al , 1999; Yin et al , 2005; Stautmane, 2012; Tas et al. , 2012; Burrows and Mooring, 2015; Dauer and Long, 2015). …”
Section: Introductionmentioning
confidence: 99%